Case Report: Pitfalls in CF screening – targeted variant analysis can cause misleading results and therapy recommendations - Karnstedt, Maike; Ahting, Simone; Behrendt, Sophie; Hove, Maike vom; Hentschel, Julia (Frontiers in Genetics, 2025)
BackgroundCystic Fibrosis (CF) is primarily diagnosed in Germany through newborn screening (NS) using immunoreactive trypsinogen (IRT)/Pancreatitis-Associated Protein (PAP) measurements and genetic testing for common CFTR gene variants. While this method is effective in identifying the most frequent mutations, it may overlook complex alleles, which can impact phenotype and treatment efficacy.Case PresentationWe report the case of a five-year-old girl diagnosed with CF through NS, initially identified as homozygous for the F508del variant. Despite early Orkambi therapy, her response was suboptimal, with high sweat chloride levels and recurrent respiratory infections. Re-sequencing with a next-generation sequencing (NGS) panel revealed an additional undetected heterozygous pathogenic variant. Upon switching to elexacaftor/tezacaftor/ivacaftor (ETI), sweat chloride levels significantly improved.ConclusionStandard genetic screening methods may fail to detect complex alleles, leading to misinterpretation of genotype and suboptimal treatment choices. This case highlights the necessity of comprehensive genetic analysis in patients with unexpected therapy responses. When CFTR modulator therapy does not yield the expected improvements, re-sequencing should be considered to optimize precision medicine approaches for CF.